(untitled) (Medical Forum Monthly, 2024)
Introduction: A study of the incidence of different type of endometrial diseases especially the endometrial hyperplasia and endometrial carcinoma in women. Objectives: Endometrial hyperplasia is idiopathic or occurs due to associated diseases or conditions. It can also be transformed in endometrial carcinoma. Histological and histochemical procedures, help in appropriate diagnosis in different types of endometrial hyperplasia, cancer and other diseases. Study Design: Retrospective study Place and Duration of study: This study was conducted at the Dept. of Pathology, DMC, DUHS, Karachi from 1st January 2006 to 31st December 2011. Materials and Methods: Total 950 Slides / paraffin blocks of endometrial biopsies from patients 20 to 70 years of age were retrospectively studied. The biopsies were received from Civil Hospital, Sindh Government Lyari General Hospital and Government Services Hospital, Karachi. Results: In present study, 950 cases of different type of endometrial diseases were included. The maximum 498 (52.42 %) cases were encountered in proliferative and secretory phases, 255 cases (26.84 %) cases of endometrial hyperplasia with 20-55 years of age and 65 (6.84 %) cases of endometrial carcinoma of 38 to 58 years of age. Conclusion: It is observed that there is increased tendency of cystic hyperplasia in endometrial hyperplasia occurring, 20 to 55 years of age. The occurrence of endometrial carcinoma is 6.84 %.